An online platform supporting the analysis of water adaptation measures in the Alps. Issue 2 (28th January 2018) - Bojovic, Dragana; Giupponi, Carlo; Klug, Hermann; Morper-Busch, Lucia; Cojocaru, George; Schörghofer, Richard
Abstract : Climate change may result in reduced water supply from the Alps – an important water resource for Europe. This paper presents a multilingual platform that combines spatial and multi-criteria decision-support tools to facilitate stakeholder collaboration in the analysis of water management adaptation options. The platform has an interactive map interface that allows participants to select a location of their interest within the Alpine Arc. By utilising the decision-support tool, stakeholders can identify suitable adaptation solutions for different geographical units, according to their experience and preference. The platform was used to involve experts across Alpine borders, domains and decision-making levels, as well as a group of university students. The experts favoured the planning instruments for saving water, while the students inclined towards the measures that would improve water conservation. The initial results confirmed the suitability of the platform for future involvement of decision-makers in spatio-temporal analyses of adaptation pathways in the Alps.